Estimation of Bullying Incidence Using Linear Regression Algorithm - Sitepu, Cindy Yohana; Pardede, A M H; Husnul Khair (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
Bullying is a violent act intended to cause harm or humiliation to another person. Bullying can take many different forms, including verbal and nonverbal, and it frequently targets people who are thought to be weaker or different. Nevertheless, because many bullying incidents go unreported, it is challenging to gather reliable statistics on the prevalence of bullying. In this study, the number of bullying cases in the field of education is estimated using a linear regression approach. This algorithm is used because it may estimate based on pertinent data, like the gender-based type of bullying and data on the quantity of bullying events that occurred in the preceding year. According to the study's findings, 2,250 bullying incidences are predicted for the upcoming year 2024, with a MAPE (Mean Absolute Percentage Error) of 0,07% or an accuracy level of 99,3%, categorized as highly accurate forecasting results.